Radical Hope as a Transformative Praxis in the Face of Hate and Intolerance - Ashley E. Nickels; Camille Tinnin (Journal of Social Equity and Public Administration)
Radical hope is a transformative approach suited to sustain collective resilience in moments of crisis and profound disorientation. In our current moment of democratic backsliding, vilification and scapegoating of people and groups, increased hate crime incidence, and increased sociopolitical polarization, radical hope offers an approach that bridges theoretical and historical insights with actionable strategies. It can serve as a catalyst for collective action, enabling communities to confront systemic oppression while imagining and constructing just alternatives. We examine four theoretical and practical dimensions of radical hope: envisioning beyond the present, collective resilience, moral anchoring, and sustained engagement. In doing so, we argue for integrating radical hope as a transformative approach, particularly for public administration scholars and practitioners as they respond to threats to democracy, including challenges to values of social equity and inclusion.